2009
DOI: 10.1099/vir.0.005041-0
|View full text |Cite
|
Sign up to set email alerts
|

Unswitched immunoglobulin M response prolongs mouse survival in prion disease

Abstract: Several studies have failed to demonstrate the presence of immune responses to infectious prions during the course of prion disease, reflecting the identical primary structure of normal and disease-associated isoforms and the widespread expression of the normal cellular form of prion protein, PrPC, leading to B- and/or T-cell tolerance of disease-associated isoforms and also possibly because antigen-presenting cells are unable to process the highly aggregated, detergent-insoluble, protease-resistant form, PrPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Brains from terminally ill scrapie-infected wild-type (WT) FVB/N mice were homogenized in PBS (10 % w/v) using an Ultra Turrax tissue homogenizer (SIS) as described previously (Tayebi et al, 2009) Immunization of camels with PrP Sc -Dynabeads. All procedures involving animals were carried out under a project and personal licence authority issued in accordance with The Animals (Scientific Procedures) Act 1986 and approval by the Institutional Ethics Committee.…”
Section: Methods Preparation Of Dynabeads-adsorbed Antigen For Immunimentioning
confidence: 99%
See 1 more Smart Citation
“…Brains from terminally ill scrapie-infected wild-type (WT) FVB/N mice were homogenized in PBS (10 % w/v) using an Ultra Turrax tissue homogenizer (SIS) as described previously (Tayebi et al, 2009) Immunization of camels with PrP Sc -Dynabeads. All procedures involving animals were carried out under a project and personal licence authority issued in accordance with The Animals (Scientific Procedures) Act 1986 and approval by the Institutional Ethics Committee.…”
Section: Methods Preparation Of Dynabeads-adsorbed Antigen For Immunimentioning
confidence: 99%
“…In more recent work (Tayebi et al, 2009), we have demonstrated that active immunization with non-denatured PrP Sc results in considerable prolongation of the incubation period and delayed onset of clinical prion disease in mice. Importantly, this study demonstrated that immunization with non-denatured PrP Sc predominantly elicits serum IgM.…”
Section: Introductionmentioning
confidence: 96%
“…However, this approach normally results in the production of IgM Abs (Tayebi et al 2004(Tayebi et al , 2009(Tayebi et al , 2011Nikles et al 2005 ;Buchholz et al 2006 ) . IgM Abs is not as useful as IgG Abs in diagnostic applications due to low af fi nity, and they are not as useful in therapeutic applications for the following reasons: IgM cannot cross the blood-brain barrier, they diffuse through the tissues poorly, they provide only short-lived immunity, and they can cause the inappropriate activation of 3Cb complement.…”
Section: Production Of Prp Sc -Speci Fi C Antibodies: Overcoming Selfmentioning
confidence: 99%
“…Unfortunately, the exposure of PrP null mice to PrP Sc proteins without the use of harsh adjuvants, carriers, or Virus Like Particles (VLPs), etc., regularly induces the production of IgM Ab in mice (Tayebi et al 2004(Tayebi et al , 2009(Tayebi et al , 2011Nikles et al 2005 ;Buchholz et al 2006 ) . This seemingly default tendency of the murine immune system to produce IgM upon exposure to PrP…”
Section: Overcoming B-cell Tolerance To Self Proteinsmentioning
confidence: 99%
“…84 Another study showed that PrPDynabeads stimulated the immune system in a murine scrapie model to produce anti-PrP immunoglobulin (Ig) M antibodies and prolonged onset after repeated immunization. 85 Some research groups have used truncated prion peptides as immunogens for the production of antibodies. However, though many modified truncated prion peptides induce an antibody response in animal models, only a few delay onset and slow progression of the disease.…”
mentioning
confidence: 99%